Comparing Surface and Fine-Wire Electromyography Activity of Lower Leg Muscles at Different Walking Speeds - Péter, Annamária; Andersson, Eva; Hegyi, András; Finni, Taija; Tarassova, Olga; Cronin, Neil; Grundström, Helen; Arndt, Anton (Frontiers in Physiology, 2019)
Ankle plantar flexor muscles are active in the stance phase of walking to propel the body forward. Increasing walking speed requires increased plantar flexor excitation, frequently assessed using surface electromyography (EMG). Despite its popularity, validity of surface EMG applied on shank muscles is mostly unclear. Thus, we examined the agreement between surface and intramuscular EMG at a range of walking speeds. Ten participants walked overground at slow, preferred, fast and maximum walking speeds (1.01±0.13, 1.43±0.19, 1.84±0.23, and 2.20±0.38 m·s-1, respectively) while surface and fine-wire EMG activities of flexor hallucis longus (FHL), soleus (SOL), medial (MG) and lateral (LG) gastrocnemii, and tibialis anterior (TA) muscles were recorded. Surface and intramuscular peak-normalised EMG amplitudes were compared for each muscle and speed across the stance phase using Statistical Parametric Mapping. In FHL, we found differences around peak activity at all speeds except fast. There was no difference in MG at any speed or in LG at slow and preferred speeds. For SOL and LG, differences were seen in the push-off phase at fast and maximum walking speeds. In SOL and TA, surface EMG registered activity during phases in which intramuscular EMG indicated inactivity. Our results suggest that surface EMG is generally a suitable method to measure MG and LG EMG activity across several walking speeds. Minimising cross-talk in FHL remains challenging. Furthermore, SOL and TA muscle onset/offset defined by surface EMG should be interpreted cautiously. These findings should be considered when recording and interpreting surface EMG of shank muscles in walking.